Magma chamber formation by magma intrusion into the Earth’s crust - Utkin, Ivan Sergeyevich; Melnik, Oleg Eduardovich (Computational Continuum Mechanics, 2018)
The main mechanism of transport of magma in the Earth’s crust is the formation of cracks (dikes), through which the melt moves toward the surface under the action of buoyancy forces and tectonic stresses. Due to the structural features of the crust or external field stresses, dikes often do not reach the surface, but penetrate the localized region in which the rocks melt, leading to the formation of magmatic chambers, whose dimensions can exceed thousands of cubic kilometers. In this article, a model based on the solution of the heat equation is presented. The model takes into account the actual melting diagrams of magma and rocks and makes it possible to investigate the process of formation of a magma chamber during the intrusion of dikes with a given flow rate. The displacement of rocks during the introduction of magma is described by an analytical solution of the problem of a plane crack located in an infinite plane under the influence of internal pressure. It is shown that, in the case of magmatic fluxes typical of island arc volcanoes, magma chambers are formed over hundreds of years from the beginning of magma intrusion. The influence of the magma flow rate, the size of the dikes and their orientation on the volume of the formed magma chamber and its shape was investigated. It is shown that, for random orientation of the dikes, spherical chambers are formed, while horizontal or vertical intrusion leads to the formation of chambers of elliptical shapes. The size of the chamber significantly exceeds the area of dike intrusion due to the displacement of magma and rocks of the crust, their warming up and melting. For large times, the boundary of the chamber remains sharp.